Faktor Predisposing, Enabling dan Reinforcing Perkawinan Dini pada Masa Pandemi Covid-19 - Hermasdito Syahsyah Rachman Syarief; Susy Katikana Sebayang (FORIKES, 2023)
During the Covid-19 pandemic there was an increase in the number of early marriages. So research is needed that aims to find out what factors are related to the occurrence of early marriage in Banyuwangi during the Covid-19 pandemic. This study applied a cross-sectional design. The research subjects were 64 women aged 10-21 years, who were randomly selected. Data was collected by filling out a questionnaire, then analyzed using the Chi-square test. The results showed that predisposing factors (economic change, respondent's knowledge, respondent's education, respondent's income, pregnancy out of wedlock and knowledge of marriage regulations), enabling factors (online schooling) and reinforcing factors (education and parental income), all correlated significantly with the incidence of early marriage (p <0.05). The factor most related to the incidence of early marriage during Covid-19 was the respondent's knowledge with OR = 31.78. It was concluded that the high number of early marriages during the Covid-19 pandemic in Muncar District, Banyuwangi Regency was related to changes in the economy, knowledge, education, respondent income, pregnancies outside of marriage, knowledge of marriage regulations, online schools and parents' education and income.Keywords: early marriage; economic changes; online school; the Covid-19 pandemic ABSTRAK Selama pandemi Covid-19 terjadi peningkatan angka perkawinan dini. Maka diperlukan penelitian yang bertujuan untuk mengetahui faktor apa saja yang berhubungan dengan terjadinya perkawinan dini di Banyuwangi pada masa pandemi Covid-19. Penelitian ini menerapkan rancangan cross-sectional. Subyek penelitian adalah 64 perempuan berusia 10-21 tahun, yang dipilih secara acak. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa predisposing factors (perubahan ekonomi, pengetahuan responden, pendidikan responden, pendapatan responden, hamil di luar nikah dan pengetahuan peraturan perkawinan), enabling factor (sekolah daring) dan reinforcing factors (pendidikan dan pendapatan orang tua), semuanya berkorelasi secara signifikan dengan kejadian perkawinan dini (p <0,05). Faktor yang paling berhubungan terhadap kejadian perkawinan dini selama Covid-19 yaitu pengetahuan responden dengan OR = 31,78. Disimpulkan bahwa tingginya angka perkawinan dini di masa pandemi Covid-19 di Kecamatan Muncar, Kabupaten Banyuwangi berhubungan dengan perubahan ekonomi, pengetahuan, pendidikan, pendapatan responden, kehamilan di luar nikah, pengetahuan peraturan perkawinan, sekolah daring serta pendidikan dan pendapatan orang tua.Kata kunci: perkawinan dini; perubahan ekonomi; sekolah daring; pandemi Covid-19